8x+4y+7z-4x+4z-5y=

Simple and best practice solution for 8x+4y+7z-4x+4z-5y= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8x+4y+7z-4x+4z-5y= equation:


Simplifying
8x + 4y + 7z + -4x + 4z + -5y = 0

Reorder the terms:
8x + -4x + 4y + -5y + 7z + 4z = 0

Combine like terms: 8x + -4x = 4x
4x + 4y + -5y + 7z + 4z = 0

Combine like terms: 4y + -5y = -1y
4x + -1y + 7z + 4z = 0

Combine like terms: 7z + 4z = 11z
4x + -1y + 11z = 0

Solving
4x + -1y + 11z = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'y' to each side of the equation.
4x + -1y + y + 11z = 0 + y

Combine like terms: -1y + y = 0
4x + 0 + 11z = 0 + y
4x + 11z = 0 + y
Remove the zero:
4x + 11z = y

Add '-11z' to each side of the equation.
4x + 11z + -11z = y + -11z

Combine like terms: 11z + -11z = 0
4x + 0 = y + -11z
4x = y + -11z

Divide each side by '4'.
x = 0.25y + -2.75z

Simplifying
x = 0.25y + -2.75z

See similar equations:

| n+3.4=8.3 | | 4y-6(y+8)=8y+12 | | 7x^2-10*x-5=0 | | -5+6j=-53 | | -1x+3=19 | | 39=-3+5(x+6) | | 7w+8=64 | | 2x-5=-(3x+7) | | 3=-6x+3(x+3) | | 19-3x=9x-5 | | 1.8+7n=4n | | y+6=5x+3xr-4 | | 9-3p=3 | | 7x+-3=-11 | | 2-7x=5x+50 | | 2x=-(3x+7) | | 25m-10=21m+14 | | 10y-7=28+3y | | -122+2x=153-9x | | 8-3w=5 | | 3x-14=-5x+34 | | 16=7b+30 | | 0.70x=455000 | | 3u-12=-21 | | 4*7v= | | 8y-3=-27 | | 3z^2+3z+1=0 | | 2x^2-3x-72=0 | | 30y^2=36y | | 2(a-8)+7=5(a+2)-3a-29 | | 9x-45=5x+135 | | (2)(5)+4= |

Equations solver categories